PENGARUH MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. RIFAN FINANCINDO BERJANGKA MEDAN - ESTER SINAGA; TOGU HARLEN LBN. RAJA; LASMAN E. BACHTIAR (LP2MTBM MAKARIOZ, 2021)
This study aims to determine how much influence motivation and organizational commitment partially and simultaneously onemployee performance at PT. Rifan Financindo Futures Medan, using this type of quantitative research. The result of thisstudy is that the partial motivation of the t-count value is -0.064 with the t-table value at a significant level = 5%, namely1.167, with a significant value of 0.949> 0.05, meaning that it has no significant effect. It also explains that motivation has nosignificant effect on employee performance at PT. Rifan Financindo Berjangka Medan or if it is related to Guilford's theory,the motivation variable is very weak in relation to employee performance. Partially, organizational commitment, thecalculated t value is 4.833 where the t table value at 5% is 1.167 which means it is positive, with a significant value of 0.000<0.005 which means it has a significant effect. This explains that organizational commitment has a positive and significanteffect on employee performance at PT. Rifan Financindo Berjangka Medan or if it is related to Guilford's theory, themotivation variable has a moderate relationship with the performance of employees at PT. Rifan Financindo Futures Medan.Based on the results of the study, the calculated F value was 13.146 with a significance value of 0.000. While the F table is3.13 at a significant level of 95% (a = 0.05), with that F count 13.146 > 3.13 which means that the independent variable hasan effect on the dependent variable. Thus, motivation and organizational commitment together have an influence onemployee performance.